TITOVO NOVO RUHO (Филолошки студии, 2019)
This work explores the presence of Tito in contemporary Croatian literature and analyzes his importance in the context of the ex Yugoslavian intercultural community. The study reveals that Tito is even more present in the virtual world of the Internet as an interesting form of auto-irony and as a particularly significant expression of the “collective unconsciousness”.